Kearifan Lokal Dalam Penanggulanganan Bencana Gempa Bumi Dan Sistem Pewarisannya di Pulau Lombok Nusa Tenggara Barat - Taufik, Mohamad Zaki; Pujayanti, Luh Putu Vera Astri (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2024)
Disasters can destroy but also provide opportunities and triggers to rise and be resilient. Active-preventive efforts are needed to minimize the impact of disasters through reactivating local knowledge and developing its inheritance system as a momentum for community resilience in facing crises. This study aims to determine the local wisdom that can reduce the impact of earthquake disasters both in the pre-, during and post-earthquake disasters and their inheritance systems on Lombok Island. Local wisdom in the pre-disaster cycle in disaster mitigation activities through the physical form of buildings and settlement patterns, myths and traditional ceremonies and disaster beliefs. In disaster preparedness, organizing reserves for food insecurity in barn buildings. In disaster early warning through reading natural signs and notification of events through local languages and beating objects that make sounds. Local wisdom in the cycle when a disaster occurs in disaster response through the placement of evacuation and victim assistance in the center of the berugak multifunctional building and disaster relief activities through besiru as the spirit and value of community cooperation. Local wisdom in the post-disaster cycle in disaster recovery through the determination and willingness of the community to rise to normal conditions by working hard, patiently and sincerely. Local wisdom in rehabilitation activities normalizes life through trauma healing with traditional games. The development of modernization, globalization and needs causes the existence of local wisdom to depend on the level of functionality and inheritance efforts from social communities on Lombok Island. Most of the ways of inheriting local wisdom in the context of earthquake disaster management are carried out through the local wisdom inheritance system of vertical transmission inheritance.